2013
DOI: 10.1097/aap.0b013e318281a348
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Blinded Study of Continuous Ropivacaine Infusion in the Median Sternotomy Incision Following Cardiac Surgery

Abstract: The phase III trial did not show improvement in time to extubation of the trachea or pain control in the 0.3% ropivacaine group, but it was stopped early by the data safety monitoring board.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…[126][127][128][129][130][131][132][133] No evidence regarding their effect on the development of chronic pain exists. 126 …”
Section: Continuous Wound Cathetermentioning
confidence: 99%
“…[126][127][128][129][130][131][132][133] No evidence regarding their effect on the development of chronic pain exists. 126 …”
Section: Continuous Wound Cathetermentioning
confidence: 99%
“…One study [17] of minimal invasive hip replacement reported no delays in wound healing and no wound infections at the 3-month follow-up visit. During the preparation of the manuscript, the previously unpublished sternotomy study suspended due to an increased wound infection rate [18] was published; this study by Agarwal et al [27] reported wound infection rates of 9.1% (4/44) for ropivacaine and 0% (0/41) for placebo. While the ropivacaine rate was not statistically different from placebo, it was significantly higher than the clinic's historical control rate and therefore resulted in premature discontinuation of the study.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that the incidence of catheter or pump failure was 1.1 %. Although it has been reported that the local anesthetic ropivacaine displays antimicrobial activity [15], a study of continuous ropivacaine infusion in the median sternotomy incision following cardiac surgery showed high infection rates (9 %, n = 44) and this rate of infection was not statistically different in the saline group (0 %, n = 41) (P [ 0.05) [16]. However, a larger sample size must be evaluated before a definitive conclusion can be drawn about the safety of this technique.…”
Section: Discussionmentioning
confidence: 99%